Role of cumulative risk factors in the development of substance abuse - Ünal, Süheyla; Aktan Mutlu, Elif; Topaktaş Yıldırım, Özgü (Journal of Dependence, 2021)
Objective: In this study, the hypothesis that the cumulative effect of possible risk factors is more effective in the development of substance addiction was tested. Method: 200 substance addicts and 200 healthy controls were included in the study. SCID-I clinical interview, sociodemographic data form, Rosenberg self-esteem scale, Parenting Styles Scale were applied to the subjects. A questionnaire was given to identify risks related to family and childhood life. 14 variables were considered as risk factors. The sample was divided into high and low risk groups. Results: After the age of 14, parental loss and separation, definition of family relationships as "bad", presence of substance addiction in family members, low self-esteem, and father’s lack of interest / acceptance were more common in substance addicts than in healthy controls. Separation from parents before the age of 13 and continuous family quarrels were reported with a higher rate in healthy controls. The effects of mother control dimension, father acceptance dimension and self-esteem were found to be high in the development of addiction. The effects of mother control dimension, father acceptance dimension and self-esteem were found to be high in the development of addiction. Discusion: When the risk factors are considered individually, the substance addiction group is disadvantaged, while the risk ratio is equalized in both groups in terms of cumulative risk factors. This situation brings to mind the concept of "resilience". The fact that healthy controls did not develop addiction was interpreted as that they might have developed appropriate coping skills against the negative living conditions they encountered from childhood. In addition to reducing risk factors in the prevention of substance addiction, it would be an appropriate approach to focus on practices that will increase resilience.